Superhydrophobic cotton fabrics prepared by sol–gel coating of TiO2 and surface hydrophobization - Chao-Hua Xue et al (Science and Technology of Advanced Materials, 2008)
By coating fibers with titania sol to generate a dual-size surface roughness, followed by hydrophobization with stearic acid, 1H,1H,2H,2H-perfluorodecyltrichlorosilane or their combination, hydrophilic cotton fabrics were made superhydrophobic. The surface wettability and topology of cotton fabrics were studied by contact angle measurement and scanning electron microscopy. The UV-shielding property of the treated fabrics was also characterized by UV-vis spectrophotometry.